Bioleft: open-source seeds for low-input farming systems - Cremaschi, Almendra (2020)
This article describes Bioleft, an ‘open source’, highly collaborative seed breeding initiative, in order to encourage reflection on potential synergies with fair trade ideas and practices. Bioleft aims to develop and redistribute collective agency over seed breeding, as a response to the emergence of an oligopolistic seed industry. It is experimenting with novel approaches to seed innovation that increase the diversity of crop varieties, in order to support agricultural practices that are ignored by mainstream seed firms, particularly smallscale family farming and more ecologically and socially sustainable agricultural practices. More generally it is experimenting with new forms of social and productive organization based on norms of sharing and solidarity.